2022
DOI: 10.3389/fphar.2022.921337
|View full text |Cite
|
Sign up to set email alerts
|

Reduning Attenuates LPS-Induced Human Unmilical Vein Endothelial Cells (HUVECs) Apoptosis Through PI3K-AKT Signaling Pathway

Abstract: The molecular mechanism of Reduning (RDN) in the treatment of sepsis was analyzed based on network pharmacology. The system pharmacology method was administered to search the active ingredients and targets of RDN, identify the sepsis-related genes, and determine the targets of RDN in the treatment of sepsis. Cytoscape was used to build a “drug component-target” network to screen key compounds. A protein-protein interaction (PPI) network was constructed using STRING, and core targets were revealed through topol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Reduning is a TCM injection composed of Artemisia annulosa, honeysuckle, and gardenia, which is recommended for the treatment of critical COVID-19 patients by "the Diagnosis and Treatment Protocol for ." Our previous studies confirmed that Reduning could improve sepsis-induced acute lung injury (SALI) by downregulating LPS-induced apoptosis of human umbilical vein endothelial cells (HUVECs) through the PI3K-AKT pathway and thereby improving vascular endothelial barrier function (Wang et al, 2022a). Existing studies have shown that, the basic treatment of Western medicine, supplemented with Reduning, could significantly improve the clinical symptoms, pulmonary function, and prognosis of patients with idiopathic fibrosis (Wang et al, 2020;Shi et al, 2022).…”
Section: Introductionmentioning
confidence: 68%
“…Reduning is a TCM injection composed of Artemisia annulosa, honeysuckle, and gardenia, which is recommended for the treatment of critical COVID-19 patients by "the Diagnosis and Treatment Protocol for ." Our previous studies confirmed that Reduning could improve sepsis-induced acute lung injury (SALI) by downregulating LPS-induced apoptosis of human umbilical vein endothelial cells (HUVECs) through the PI3K-AKT pathway and thereby improving vascular endothelial barrier function (Wang et al, 2022a). Existing studies have shown that, the basic treatment of Western medicine, supplemented with Reduning, could significantly improve the clinical symptoms, pulmonary function, and prognosis of patients with idiopathic fibrosis (Wang et al, 2020;Shi et al, 2022).…”
Section: Introductionmentioning
confidence: 68%
“…Activation of the PI3K-AKT-mTOR pathway could alleviate the apoptosis of HUVECs ( Lin et al., 2020 ; Chen et al., 2021 ). In addition, our previous study revealed that various active components in Reduning, a traditional Chinese medicine, could alleviate LPS-induced apoptosis of HUVECs by targeting AKT1 and activating AKT phosphorylation ( Wang et al., 2022 ). The discovery of AKT dates back to the 1970s, when an oncogene sequence, named AKT8, was identified in murine leukemia viruses, and two homologous oncogenes of AKT8, named AKT1 and AKT2 (also known as PKKB αand PKKB β, respectively), were subsequently identified in human chromosomes ( Pastorino et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are 3 isoforms of AKT-AKT1, AKT2, and AKT3-among which AKT1 is most closely connected to apoptosis (Green et al, 2013;Gong et al, 2017;Kim et al, 2020). Previous studies have confirmed that pyrotoxin could improve apoptosis of LPSinduced HUVECs by promoting AKT1 phosphorylation (Wang et al, 2022). Currently, the only activator targeting AKT is SC79, which binds to the pleckstrin homology (PH) domain of AKT at residue 25 (arginine) (Jo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tang et al stated that RDN can improve lung inflammation and oxidative stress by down-regulating the nuclear factor (NF)-kB pathway (15). Yang et al found that RDN ameliorated LPS-induced ALI through decreased phosphorylation of extracellular regulated protein kinase (ERK)1/2 to suppress the formation of neutrophil extracellular traps (NETs) (16). In our previous research, we found that the activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway by RDN could reduce the lipopolysaccharide (LPS)induced apoptosis of human umbilical vein endothelial cells (HUVECs) (17).…”
Section: Introductionmentioning
confidence: 99%
“…found that RDN ameliorated LPS-induced ALI through decreased phosphorylation of extracellular regulated protein kinase (ERK)1/2 to suppress the formation of neutrophil extracellular traps (NETs) ( 16 ). In our previous research, we found that the activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway by RDN could reduce the lipopolysaccharide (LPS)-induced apoptosis of human umbilical vein endothelial cells (HUVECs) ( 17 ). In this study, we further explored the underlining mechanisms by which RDN can inhibit apoptosis through the AKT pathway.…”
Section: Introductionmentioning
confidence: 99%